Forensic Approach to Optimise Children’s Right to Opinion in Indonesian Courts - Ohoiwutun, Y.A. Triana; Prabhata, Evoryo Carel; Chatterjee, Pyali (Lentera Hukum, 2023)
Various attempts to accommodate a child's opinion in courts have proven successful, and this participation has been increasingly regarded as integral to children's rights. However, the issue remains problematic, particularly in the Global South countries like Indonesia. This paper examines the legal and regulatory framework of protecting children in Indonesia to comply with children's right to opinion and how this right is implemented. Then, it demonstrates the significant role of forensic science in complementing legal inquiry to consider a child's opinion in court. Using policy-oriented study and doctrinal research with qualitative analysis and, to some extent, a comparative perspective, this paper elaborates on Indonesia's experience in protecting children's right to opinion with legislation in India, particularly dealing with child sexual offences. This study shows that Indonesia's legal and regulatory framework of children protection had not specified to elucidate children's right to an opinion, particularly in the Child Protection Law, the primary legal basis for children protection. Also, Indonesia is yet to have a robust and consistent practice of human rights-based instruments considered in the court, indicated by a lack of comprehensive understanding in law enforcement to implement this right. While the interpretation in law enforcement is essential to be optimised toward child-oriented resolution, taking the child's opinion in court promotes human rights practice in Indonesia. Compared to adults, children are complex, particularly in a case of a child victim of rape-related pregnancy. The forensic approach can be an alternative by involving forensic experts in courts to consider a child's psychology and physical condition.Keywords: Children's Rights, Forensic Science, Indonesian Courts, Right to Opinion.